Front Cover: Structural Basis of Substrate Recognition and Covalent Inhibition of Cdu1 from Chlamydia trachomatis (ChemMedChem 19/2018). (9th October 2018) - Ramirez, Yesid A.; Adler, Thomas B.; Altmann, Eva; Klemm, Theresa; Tiesmeyer, Christian; Sauer, Florian; Kathman, Stefan G.; Statsyuk, Alexander V.; Sotriffer, Christoph; Kisker, Caroline
Abstract : The Front Cover shows a covalent inhibitor (orange) simultaneously addressing the active sites of the Chlamydia trachomatis deubiquitylase 1 (Cdu1, green) and the adenovirus protease (adenain, red). The covalent bond is highlighted in yellow. The structural similarities of evolutionarily related proteases have been successfully harnessed for the repurposing of adenain inhibitors on Cdu1, demonstrating the potential of target‐hopping for the development of deubiquitylase (DUB) inhibitors. More information can be found in the Full Paper by Caroline Kisker, Christoph Sotriffer et al. onpage 2014 in Issue 19, 2018 (DOI:10.1002/cmdc.201800364 ).